2014
DOI: 10.4038/ijms.v1i2.53
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical tag-set for rule-based processing of Tamil language

Abstract: Corpora are fundamental tools for Natural Language Processing. Part of Speech tagging provides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In grammar books written by native grammarians (Thesikar 1957;Senavaraiyar 1938) Tamil words have been primarily divided into four types, namely: nouns, verbs-intensifiers/attributives, and particles. However, more recently there have been more granular Part of Speech (POS) analyses proposed by Sarveswaran and Mahesan (2014); Baskaran et al (2008); Lehmann (1993). We follow Lehmann (1993) and Sarveswaran and Mahesan (2014) closely.…”
Section: Part Of Speechmentioning
confidence: 99%
See 1 more Smart Citation
“…In grammar books written by native grammarians (Thesikar 1957;Senavaraiyar 1938) Tamil words have been primarily divided into four types, namely: nouns, verbs-intensifiers/attributives, and particles. However, more recently there have been more granular Part of Speech (POS) analyses proposed by Sarveswaran and Mahesan (2014); Baskaran et al (2008); Lehmann (1993). We follow Lehmann (1993) and Sarveswaran and Mahesan (2014) closely.…”
Section: Part Of Speechmentioning
confidence: 99%
“…However, more recently there have been more granular Part of Speech (POS) analyses proposed by Sarveswaran and Mahesan (2014); Baskaran et al (2008); Lehmann (1993). We follow Lehmann (1993) and Sarveswaran and Mahesan (2014) closely. These are relatively less granular when compared to others, but we have found that these allow for the most accurate analysis in our implementation.…”
Section: Part Of Speechmentioning
confidence: 99%
“…Part of Speech (POS) tagging is an important phase in the parsing process where each word in a sentence is assigned with its POS tag (or lexical category) information. Several attempts have been made to define POS tagsets for Tamil, based on different theories, and level of granularity; (Sarveswaran and Mahesan, 2014) gives an account of different tagsets. Among these, Amrita (Anand Kumar et al, 2010) and BIS 5 are two popular tagsets.…”
Section: Pos Tagging Using Thamizhipostmentioning
confidence: 99%